Maternal Nutritional Deficiencies and Small-for-Gestational-Age Neonates at Birth of Women Who Have Undergone Bariatric Surgery - J. Hazart; D. Le Guennec; M. Accoceberry; D. Lemery; A. Mulliez; N. Farigon; C. Lahaye; M. Miolanne-Debouit; Y. Boirie (Journal of Pregnancy)
The aim is to compare the prevalence of maternal deficiencies in micronutrients, the obstetrical and neonatal complications after bariatric surgery according to surgical techniques, the time between surgery and conception, and BMI at the onset of pregnancy. A retrospective cohort study concerned 57 singleton pregnancies between 2011 and 2016 of 48 adult women who have undergone bariatric surgery. Small-for-gestational-age neonates were identified in 36.0% of pregnancies. With supplements intake (periconceptional period: 56.8%, trimester 1 (T1): 77.8%, T2: 96.3%, and T3: 100.0%), nutritional deficiencies involved vitamins A (T1: 36.4%, T2: 21.1%, and T3: 40.0%), D (T1: 33.3%, T2: 26.3%, and T3: 8.3%), C (T1: 66.7%, T2: 41.2%, and T3: 83.3%), B1 (T1: 45.5%, T2: 15.4%, and T3: 20.0%), and B9 (T1: 14.3%, T2: 0%, and T3: 9.1%) and selenium (T1: 77.8%, T2: 22.2%, and T3: 50.0%). There was no significant difference in the prevalence of nutritional deficiencies and complications according to surgery procedures and in the prevalence of pregnancy issues according to BMI at the beginning of the pregnancy and time between surgery and pregnancy. Prevalence of micronutritional deficiencies and small-for-gestational-age neonates is high in pregnant women following bariatric surgery. Specific nutritional programmes should be recommended for these women.